Elevated expression of SLC34A2 inhibits the viability and invasion of A549 cells - YANG, WEIHAN (D.A. Spandidos, 2014)
Abnormal expression of solute carrier family 34 (sodium phosphate), member 2 (SLC34A2) in the lung may induce abnormal alveolar type II (AT II) cells to transform into lung adenocarcinoma cells, and may also be important in biological process of lung adenocarcinoma. However, at present, the effects and molecular mechanisms of SLC34A2 in the initiation and progression of lung cancer remain to be elucidated. To the best of our knowledge, the present study revealed for the first time that the expression levels of SLC34A2 were downregulated in the A549 and H1299 lung adenocarcinoma cell lines. Further investigation demonstrated that the elevated expression of SLC34A2 in A549 cells was able to significantly inhibit cell viability and invasion in vitro. In addition, 10 upregulated genes between the A549-P-S cell line stably expressing SLC34A2 and the control cell line A549-P were identified by microarray analysis and quantitative polymerase chain reaction, including seven tumor suppressor genes and three complement genes. Furthermore, the upregulation of complement gene C3 and complement 4B preproprotein (C4b) in A549-P-S cells was confirmed by ELISA analysis and was identified to be correlated with recovering Pi absorption in A549 cells by the phosphomolybdic acid method by enhancing the expression of SLC34A2. Therefore, it was hypothesized that the mechanisms underlying the effect of SLC34A2 on A549 cells might be associated with the activation of the complement alternative pathway (C3 and C4b) and upregulation of the expression of selenium binding protein 1, thioredoxin-interacting protein, PDZK1-interacting protein 1 and dual specificity protein phosphatase 6. Downregulation of SLC34A2 may primarily cause abnormal AT II cells to escape from complement-associated immunosurveillance and abnormally express certain tumor-suppressor genes inducing AT II cells to develop into lung adenocarcinoma. The present study further elucidated the effects and mechanisms of SLC34A2 in the generation and development of lung cancer.